KEPENTINGAN INDONESIA AKTIF DALAM CTI (Coral Triangle Initiative) - Magdalena.M, Tetty; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of this research is to observe Indonesian’s interest active in CTI (Coral Triangle Initiative) from 2006-2015. Indonesia as a maritime country with 17.504 islands and coral reefs which reached 50 875 km² made Indonesia be the one of marine biodiversity. Coral reefs have dominant contributed to Indonesia. Based on benefits of coral reefs and condition of the reefs that three quarters under threatened, Susilo Bambang Yudhoyono as a President has initiated CTI (Coral Triangle Initiative) and invited Philippines, Malaysia, Solomon Islands, Timor Leste and Papua New Guinea to cooperating. The fifth countries are also has a lot of coral reefs and located in the Asia-Pacific.This research theoretically has built with Pluralist perspective on international relations. This research is qualitative research which is used by library observation. Data which is gotten and collected through the journal books, the last thesis and then from internet has related to the problems.Researcher has formulated answered-hypothesis which reveals that Indonesia is active in CTI (Coral Trianngle Initiative) from 2006-2015 because Indonesia has political’s interest relating to border security and political imagery; economic’s interest with benefits arising from the utilization of coral reefs both as a medicine and as a tourist attraction that brings many advantages. But illegal fishing and destructive fishing in marine biodiversity and undermine ecosystem; and the Environment’s interest based on amount of abrasion that occurs as a result of damaged coral reefs as well as extreme climate change that also contributes to the destruction of coral reefs that requires action from the six countries to overcome that build commitment to each region to establish marine protected areas for ecosystem restoration.Keywords : CTI (Coral Triangle Initiative), Six Countries, National Interest, CTI-CFF(Coral Triangle Initiative on Coral Reefs, Fisheries and Food Security)